Improving Students’ Tenses Mastery Through Substitution Drill - Yuriatson Jubhari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2018)
Abstract The study focused on the use of substitution drill technique to improve the students’ mastery of tenses - simple present and past tense - which were most of students still got into trouble in learning them, particularly when to put of verb-s/es, verb 1, verb 2 and also the auxiliary verb such as do, does and did. Therefore, this study is an endeavor to examine efficacy of applying the substitution drill to enhance the junior high-school students’ mastery of tenses. This study applied pre-experimental design employing one group pretest and posttest. The participants consisted of 27 the third-grade students’ SMP Ammana Gappa Makassar, South Sulawesi. The researcher used t-test analysis to find out whether or not the use of substitution drill can improve the students’ mastery of tenses. The result of the study indicated that there were differences between students’ achievement of tenses mastery in pretest and posttest. It was proved by the value of t-test was greater than the value of t-table (22.24>2.056) with the level of significance (P) = 0, 05 and degree of freedom (N-1) = 26. The mean score of the posttest (71.62) was higher than the mean score of pretest (52.44). It may conclude that the implementation of the substitution drill as a teaching technique of tenses in SMP Amanna Gappa could improve the student’s mastery of the tenses.